An Overview on Patient-Centered Clinical Services - Gaurav Joshi; Atul Kabra; Nishant Goutam; Alka Sharma (Borneo Journal of Pharmacy, 2021)
Drug-related problems (DRPs) had often been a concern in the system that needed to be detected, avoided, and addressed as soon as possible. The need for a clinical pharmacist becomes even more important. He is the one who can not only share the load but also be an important part of the system by providing required advice. They fill out the patient's pharmacotherapy reporting form and notify the medical team's head off any drug-related issues. General practitioners register severe adverse drug reactions (ADRs) yearly. As a result of all of this, a clinical pharmacist working in and around the healthcare system is expected to advance the pharmacy industry. Its therapy and drugs can improve one's health quality of life by curing, preventing, or diagnosing a disease, sign, or symptom. The sideshows, on the other hand, do much harm. Because of the services they offer, clinical pharmacy has grown in popularity. To determine the overall effect and benefits of the emergency department (ED) clinical pharmacist, a systematic review of clinical practice and patient outcomes will be needed. A clinical pharmacist's anatomy, toxicology, pharmacology, and medicinal chemistry expertise significantly improves a patient's therapy enforcement. It is now important to examine the failure points of healthcare systems as well as the individuals involved.